Building capacity among climate adaptation planning and financial institutions for climate-resilient development using Climate Smart Governance (CSG) Dashboard, Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Dickowita, Ranoja (International Water Management Institute, 2025)
The training workshop on the Climate Smart Governance (CSG) Dashboard brought together officials from the National Planning Department (NPD) and the Climate Change Secretariat (CCS) from the Ministry of Finance, as well as from the Ministry of Environment, to strengthen evidence-based climate planning in Sri Lanka. The CSG Dashboard, developed jointly by IWMI, NPD, and CCS and launched in April 2024, integrates multi-hazard risks, vulnerability profiles, socio-economic indicators, and project data to support climate-resilient decision-making. Opening remarks from NPD highlighted the platform’s role in addressing the growing impacts of climate change on national development priorities and its importance for transparent climate investment tracking, particularly following recent international assessments. During the training, participants received a live demonstration of the dashboard’s key modules, Country Overview, Climate Outlook, Project Tracker, Geo-Intelligence, and Monitoring & Evaluation, gaining hands-on experience in navigating tools and visualizations that enable more informed planning. The discussion session generated valuable recommendations, including the need for enhanced data integration, clearer indicators, improved validation mechanisms, and stronger links to NDCs and national climate strategies. Participants emphasized real-time data incorporation, expanded training, and strengthened institutional collaboration to operationalize the tool more effectively. The workshop concluded by reaffirming the dashboard’s potential as a national decision-support platform and the importance of continuous feedback and cross-agency coordination.